Next-generation point-of-care testing in pediatric human immunodeficiency virus infection facilitates diagnosis and monitoring of treatment. Issue 27 (8th July 2022) - Bengu, Nomonde; Mchunu, Noxolo; Mokhethi, Sijabulile; Fillis, Rowena; Cromhout, Gabriela; Lobenstein, Jeroen van; Graza, Yeney; Kapongo, Constant; Chinniah, Kogielambal; Bhoola, Roopesh; Adland, Emily; Puertas, Mari C.; et al.
Abstract : Point-of-care (PoC) testing facilitates early infant diagnosis (EID) and treatment initiation, which improves outcome. We present a field evaluation of a new PoC test (Cepheid Xpert® HIV-1 Qual XC RUO) to determine whether this test improves EID and assists the management of children living with human immunodeficiency virus (HIV) infection. We compared 2 PoC tests with the standard-of-care (SoC) test used to detect HIV infection from dry blood spots in newborn infants at high risk of in utero infection. We also evaluated the ability of the PoC tests to detect HIV total nucleic acid (TNA) in children living with HIV infection who had maintained undetectable plasma viremia following very early combination antiretroviral therapy (cART) initiation. Qualitative (Qual) detection of HIV using the Xpert® HIV-1 Qual XC RUO ("RUO") and Xpert® HIV-1 Qual ("Qual") PoC tests was compared in 224 infants with the SoC DBS Roche COBAS® HIV-1/HIV-2 qualitative test. The same 2 PoC tests were also evaluated in 35 older children who had initiated cART before 21 days of age and maintained undetectable plasma viremia for a mean of 25 months. No discrepancies were observed in detection of HIV infection via the 2 PoC tests or the SoC test in the 224 neonates studied, but only 95% of the SoC test results were generated compared with 100% of the PoC test results ( P = .0009). The cycle threshold values for the research use only (RUO) assay were the lowest of the 3 assays ( P < .0001 in each case). In 6 of the 35 early-treated aviremic children, HIV TNA was detected by RUO but not Qual. The RUO assay outperforms Qual in detecting HIV-1 infection. RUO would therefore potentially improve EID and assist in identifying cART-adherent early-treated children with the lowest HIV TNA levels and the highest HIV cure potential.